Sončne celice v debeloplastni tehnologiji - Pavlin, Marko (Vakuumist, 1996)
Historical invention and solar cells research is introduced with several facts. Technology and materials for cell manufacturing are presented. Thick film technology with three major steps (print, dry, fire) are chosen. Pastes preparation and production steps are described. Basic materials are CdTe and CdS, electrode materials are carbon and indium, substrate is borsilicate glass.
Keywords: sončne celice; izdelava; zgodovinski prikazi